Legal Analysis of Child Protection Against Illegal Child Trafficking Practices - Hasibuan, Lidya Rahmadani; Nasution, Chairuni; Br. Sianturi, Laura Enggelina (CV Raskha Media Group, 2025)
The illegal practice of child trafficking is a serious crime that violates human rights and threatens the physical, psychological, and social development of children. Children, as a vulnerable group, often become victims of sexual exploitation, economic exploitation, illegal adoption, and other forms of organized crime. This study aims to analyze legal protection for children in the illegal practice of child trafficking and to assess the effectiveness of applicable legal regulations in preventing and addressing it. The research method used is normative legal research with a legislative, conceptual, and case-based approach, through a review of national laws and regulations, international legal instruments, and relevant legal doctrines and literature. The results of the study indicate that Indonesia has adequate legal instruments, such as the Child Protection Law and the Law on the Eradication of the Crime of Trafficking in Persons, which emphasize the state's obligation to protect children from all forms of exploitation. However, in practice, various obstacles remain, including weak law enforcement, lack of coordination between relevant institutions, and the suboptimal fulfillment of the rights of child victims, particularly in the aspects of recovery and rehabilitation. Therefore, strengthening legal implementation, increasing the role of law enforcement officials, and synergy between the government, the community, and child protection agencies are necessary to ensure effective legal protection for children from the illegal practice of child trafficking.